Santa María 1907. La marcha ha comenzado (Pedro Prado, 2014). The Contribution of the Visual: The Emergence of a Collective Subject - Mac-Millan Kuthe, Mary (Eikón / Imago, 2024)
In this work we approach the graphic novel by Pedro Prado entitled: Santa María 1907. The march has begun (2014). Prado tackles one of the most infamous historical events in Chilean memory: the massacre of the workers at the Domingo Santa María school in Iquique in 1907. We are guided by the question of the contribution of the visual understood as a representation with characteristics typical of the comic book medium. The analysis focuses on the specific techniques through which a clear emergence of a collective subject is achieved (double page spread, full page cartoon, use of planes, focalization). Secondly, the resource of animalization and its possible function within the logic of the novel are considered. The analysis is closed by verifying the temporality of duration as resistance through the use of an elongated vignette. Prado’s options enhance the collective aspect of the march, humanize the victims, and announce a new legibility.